Performance Improvement in Pile Anchor System for Deep Foundation Excavation Using Electroosmotic Chemical Treatment - Lei Zhang; Bing-Hui Wang; Li-Yan Wang; Li-Ping Jing; Chen Fang; Zhen-Dong Shan (Advances in Civil Engineering)
Anchoring force is vital to ensure the acceptable performance of a pile anchor system when supporting deep foundation excavation. The soft soil has several physical properties, such as low shear strength, high water content, large void ratio, and high flowability. Traditional grouting and anchoring techniques have demonstrated technical limits to deal with these soil properties in engineering projects, and accordingly, the anchoring force in the pile anchor system is difficult to meet design requirements. This paper conducted an experimental investigation on the performance improvement in a pile anchor system using the electroosmotic chemical treatment method, with an emphasis on the deep foundation application. Experimental tests and field studies were designed to enhance anchor capacity of a pile anchor system using self-designed devices. The laboratory experiments utilized a simplified anchor system in which anchors were designed as the electrodes to conduct the electroosmotic chemical treatment and consolidate the soft marine soil collected from the project site. In addition, static load tests were conducted on the tested soil to measure the anchoring force. Finally, parametric analyses were performed to investigate effects of several parameters on anchoring force in terms of the ultimate pull-out capacity of the anchor, identifying critical parameters for the field study. Based on laboratory test results, field studies were carried out in the Yingkou city. The results from field studies were compared with laboratory test results to validate feasibility of electroosmotic chemical treatment for a pile anchor system.